Comparative study of closed reduction vs. open reduction fixed with k-wiring in type 3 displaced supracondylar fractures in children - D. V., Mahesh; C. D., Deepak; Ravoof, Abdul; ., Shruthikanth (International Journal of Research in Orthopaedics, 2017)
Background: Among all the fractures in upper limb in children, supracondylar fractures of the humerus are more common injuries. In general the fractures of children are treated conservatively. But the management of supracondylar fractures has evolved over years from conservative to more aggressive approach operative techniques. Methods: The study was conducted in children's presenting with type 3 Gartland supracondylar fractures to Adichunchanagiri Institute of Medical Sciences, B. G. Nagara between January 2014 to December 2016. Results: The study consisted of 40 type 3 supracondylar fractures cases. Group A (closed reduction) had 25 cases, among them were 20 males and 5 were females. Group B (open reduction) had 15 cases among them 12 males and 3 female cases. The patients were between the age of 6 to12 years. In Group A, 19 children were in the age group of 6-10 years where as Group B had 12 cases. In Group A, 6 were in the age group of 10-12 years and 3 cases in Group B. Among the 25 cases in Group A, 19 were left sided and 6 were right sided. In group B, 11 were left sided and 4 were right sided. All patients had achieved clinical and radiological union at 4 weeks. Conclusions: Closed reduction and k-wiring had very good results for type 3 supracondylar fractures of humerus in children than conservative/open reduction methods. However for cases which we didn't get proper/satisfactory reduction in closed method, open method with triceps splitting approach was used.